2020
DOI: 10.1029/2019jc015338
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Turbulent Mixing Produced by Vertical Shear Between the Brazil Current and the Intermediate Western Boundary Current

Abstract: An intensification of the vertical shear is observed below the surface mixed layer at 21 • S due to the mutually opposing flows of the Brazil Current and the Intermediate Western Boundary Current. The propensity to develop turbulence and mixing due to vertical shear over intense stabilizing density gradients is an important characteristic of such environments. For the first time, microscale measurements were made in the Brazil Current-Intermediate Western Boundary Current system, providing direct quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 67 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…Low PV values are prone to instabilities (D'Asaro et al, 2011;Thomas et al, 2008Thomas et al, , 2013. Here, we evaluate the two-dimensional PV (e.g., Lazaneo et al, 2020;Napolitano et al, 2021;Ramachandran et al, 2018;Thomas et al, 2016) from the objectively mapped field. If one assumes that the features are indeed SCVs and that the sampling of the SCV currents and density occurs through their centers, then an approximation of the Ertel PV is possible.…”
Section: The Scv Vertical Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Low PV values are prone to instabilities (D'Asaro et al, 2011;Thomas et al, 2008Thomas et al, , 2013. Here, we evaluate the two-dimensional PV (e.g., Lazaneo et al, 2020;Napolitano et al, 2021;Ramachandran et al, 2018;Thomas et al, 2016) from the objectively mapped field. If one assumes that the features are indeed SCVs and that the sampling of the SCV currents and density occurs through their centers, then an approximation of the Ertel PV is possible.…”
Section: The Scv Vertical Structurementioning
confidence: 99%
“…For this study, we chose segments of the water column corresponding to 1 s to convert temporal derivatives to spatial derivatives, assuming a frozen field hypothesis (Taylor, 1938). Lazaneo et al (2020) showed that there is no significant ɛ variation from the different lengths of segments. Since the VTR presents very abrupt changes of depth, using a bin size of 1 s to estimate ɛ provides a reasonable number of values, mainly over shallow regions.…”
Section: Pathway For Energy Dissipationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10b shows the Ilhéus Anticyclone being formed by the bifurcation of the 14°S band; the Royal‐Charlotte Anticyclone being formed by the BC and the 18°S SSEC band; and the Abrolhos Anticyclone being formed by the BC and the 21°S SSEC band. The latter band simply adds volume to the BC, as this boundary current reattaches itself to the continental slope south of the Vitória‐Trindade Ridge crossing (e.g., Lazaneo et al., 2020; Napolitano et al., 2021).…”
Section: The Annual Cyclementioning
confidence: 99%
“…Recently, the physics of submesoscale turbulence has attracted great attention as it is not well understood due to the difficulty and challenge in observing submesoscale dynamics (McWilliams, 2016). Recent literature has reported that submesoscale processes play a crucial role in the forward energy transfer from the geostrophic scale toward dissipation (e.g., Cao et al., 2021; Capet et al., 2008a; D’Asaro et al., 2011; Jing et al., 2021; Kaneko et al., 2013; Lazaneo et al., 2020; McWilliams, 2016; Thomas et al., 2008; Wang et al., 2018; Zhang et al., 2016) and highlighted their importance to the vertical transport of heat, salt, and nutrients, which ultimately is important for biological dynamics (e.g., Lévy et al., 2012, 2001; Mahadevan & Tandon, 2006; Rosso et al., 2014; Siegelman et al., 2020; Su et al., 2018).…”
Section: Introductionmentioning
confidence: 99%